1995
DOI: 10.1111/j.1365-2044.1995.tb05925.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of isoflurane on a continuous infusion of mivacurium

Abstract: SummarySixty surgical patients were studied to evaluate the neuromuscular effects of mivacurium 0.15mg.kg-1 (2 x EDg5) for tracheal intubation. After intubation the patients were randomly allocated to receive afentanil with either propofol (starting with 9mg.kg-I h-l, reducing to 6mg.kg-I h-I after 20min)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…from late pregnancy into the early postpartum period. When the duration of action of mivacurium and the average infusion rate demonstrated in this study were compared with studies in non-pregnant normal adults, results were similar in two recent studies 15,16 but mivacurium requirement was significantly less in three other studies 3,4,18 . The different anaesthetic techniques employed may have contributed to these differences.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…from late pregnancy into the early postpartum period. When the duration of action of mivacurium and the average infusion rate demonstrated in this study were compared with studies in non-pregnant normal adults, results were similar in two recent studies 15,16 but mivacurium requirement was significantly less in three other studies 3,4,18 . The different anaesthetic techniques employed may have contributed to these differences.…”
Section: Discussionsupporting
confidence: 75%
“…It has been shown that volatile agents such as enflurane 18 , isoflurane 16 and nitrous oxide but not halothane 19 potentiate the effects of mivacurium in normal adults. To prevent patients' awareness before regaining adequate muscle power, in our study enflurane was continued after the operation ended until the TOFR returned to 70%.…”
Section: Discussionmentioning
confidence: 99%
“…8 In one study, isoflurane did not alter mivacurium infusion rates compared with propofol. 9 One possible explanation is that potentiation with volatile agents takes time to develop, because of the time taken for equilibrium of the agent with muscle tissue. 10 Sevoflurane has been reported to potentiate blockade produced by mivacurium, 11 rocuronium, 5,7 vecuronium, 12 and cisatracurium, 4 but the effect is not always consistent.…”
Section: Méthode : Chez 48 Patients Consentants Classifiés Asa I Ou mentioning
confidence: 99%